LEGAL CERTAINTY LANDRIGHTS HOLDERS IN THE TRANSITION FROM CONVENTIONAL LAND CERTIFICATES TO ELECTRONIC LAND CERTIFICATES - Revalina Gita Ananda (Law Research Review Quarterly, 2026)
Advances in information technology have driven the modernization of land administration through the implementation of electronic land certificates as part of digital public service transformation. Data from the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) shows that by 2025, 5,581,403 electronic certificates have been issued across 486 Land Offices in Indonesia. This transition raises concerns regarding legal certainty for land rights holders. This study aims to analyze the urgency of legal certainty and how it is realized in the transition process. Using an empirical legal method with a qualitative approach, the research was conducted at the Semarang City Land Office, notary offices, and law firms through observation, interviews, document analysis, and literature review. The study applies the theory of legal certainty by Gustav Radbruch and the theory of the nature of the state’s operations by Nonet and Selznick. The findings show that legal certainty is essential to ensure clarity of the subject, object, and status of land rights. Electronic certificates have equal legal validity to conventional ones, supported by integrated data, electronic signatures, unique codes, and secure digital storage, thereby improving both legal certainty and administrative efficiency.